3D ordered macroporous Pt/ZnS@ZnO core-shell heterostructure for highly effective photocatalytic hydrogen evolution. (8th May 2022) - Ji, Xinfei; Xu, Haiping; Liang, Shudong; Gan, Lei; Zhang, Rongbin; Wang, Xuewen
Abstract: ZnO, as a typical n-type semiconductor catalyst with low cost and high electron mobility, is concerned by numerous pursuers in the field of photocatalysis. However, because of its poor photo-reduction ability and high recombination rate, the ZnO in photocatalytic H2 evolution is greatly limited. To acquire an outstanding photocatalytic H2 evolution performance, 3D ordered macroporous (3DOM) ZnO is sulfurized in-situ to construct 3DOM ZnS@ZnO heterostructure. The ordered macroporous structure not only accelerates the migration of electrons and ions but also curtails the shift space of electrons and holes. The multi-junction assemblage between ZnO and ZnS effectively decreases the recombination of electron-hole pairs and improves the photo-redox capacity. The 3DOM Pt/ZnS@ZnO heterostructure exhibiting an excellent performance is 87.6 μmol g −1 h −1 in pure water. Therefore, our research presents an innovative procedure for designing other porous heterostructure photocatalysts. Graphical abstract: Image 1 Highlights: 3DOM ZnS@ZnO core-shell heterostructure is perfectly constructed. The 3DOM Pt/ZnS@ZnO exhibits an improved photocatalytic H2 evolution rate. The ordered macroporous framework improves mass transfer efficiency.